Synthesis and characterization of novel thieno[3, 2-b]thiophene based metal-free organic dyes with different heteroaromatic donor moieties as sensitizers for dye-sensitized solar cells. (January 2017) - Fernandes, Sara S.M.; Castro, M. Cidália R.; Mesquita, I.; Andrade, L.; Mendes, A.; Raposo, M. Manuela M.
Abstract: Four novel heterocycle dyes3a -d were synthesized in order to study the variations produced in the optical, electronic and photovoltaic properties by substitution of different electron-rich heterocyclic groups to the thieno[3, 2- b ]thiophene system. The final push-pull conjugated dyes3a -d were synthesized by Suzuki-Miyaura coupling reaction followed by Knoevenagel condensation of the corresponding aldehyde precursors with cyanoacrylic acid2a -d . These new push-pull systems are based on a thieno[3, 2- b ]thiophene spacer, a cyanoacetic acid anchoring group and several electron-rich heterocycles (thiophene, pyrrole and furan) as donor groups. The multidisciplinary study concerning the optical, redox and photovoltaic characterization of the dyes reveals that compound3b bearing a hexyl-bithiophene donor group/heterocyclic spacer exhibits the best overall conversion efficiency (2.49%) as sensitizer in nanocrystalline TiO2 dye sensitized solar cells. Co-adsorption studies betweenN719 and3b revealed that upon addition ofN719 co-adsorbent, the optimized cell efficiencies were improved by 16–77%. The best efficiency was 4.40%, corresponding to 54% of the photovoltaic performance of theN719 -based DSSC fabricated and measured under similar conditions. Graphical abstract: